Peptide-modified dendrimer nanoparticles for targeted therapy of colorectal cancer - Carvalho, M. R. (2019)
Peptides have recently emerged as a promising class of targeting ligands forspecific drug delivery in cancer treatment, which avoid undesirable side effectsof the systemic administration of chemotherapeutics. Their conjugation withnanoparticles has been demonstrated to improve the functionality of peptidesresulting in a versatile platform for biomedical applications. In this work, thedevelopment of carboxymethylchitosan/poly(amidoamine) (CMCht/PAMAM)dendrimer nanoparticles functionalized with YIGSR laminin receptor bindingpeptide for the active targeting and specific delivery of therapeutic agents intocolorectal cancer cells is described. The successful functionalization isconfirmed by several physico-chemical characterization techniques. Theselectivity of the YIGSR-CMCht/PAMAM dendrimer nanoparticles is firstvalidated in vitro using a micropatterned array of 67 kDa laminin receptor.Next, the specificity of YIGSR-CMCht/PAMAM dendrimers nanoparticlestoward laminin receptor is further confirmed both in 2D and 3D settings usingHCT-116 colorectal cancer cells and L929 fibroblasts in co-culture. Finally,gemcitabine-loaded YIGSR-CMCht/PAMAM dendrimer nanoparticles inducea targeted mortality on HCT-116 cancer cells in a co-culture scenario. Overall,the study shows solid evidence that YIGSR laminin receptor binding peptidecoupled to CMCht/PAMAM dendrimer nanoparticles may be employed as ananticancerous target for the specific and intracellular delivery ofchemotherapeutic agents.